Gray–white matter contrast reversal on T1-weighted spin-echo in postmortem brain - Kojima, Masatoshi; Makino, Yohsuke; Yamaguchi, Rutsuko; Motomura, Ayumi; Yajima, Daisuke; Inokuchi, Go; Saito, Naoki; Torimitsu, Suguru; Hoshioka, Yumi; Urabe, Shumari; Yoshida, Maiko; Iwase, Hirotaro; et al. (Forensic science international, 2024)
The image contrast of postmortem magnetic resonance imaging (MRI) may differ from that of antemortem MRI because of circulator arrest, changes in postmortem tissue, and low-body-temperature scanning conditions. In fact, we have found that the signal intensity of white matter (WM) on T1-weighted spin-echo (T1WSE) images of the postmortem brain was lower than that of gray matter (GM), which resulted in image contrast reversal between GM and WM relative to the living brain. However, the reason for this phenomenon is unclear. Therefore, the aim of this study is to clarify the reason why image contrast reversal occurs between GM and WM of the postmortem brain. Twenty-three corpses were included in the study (mean age, 60.6 years; range: 19–60 years; mean rectal temperature at scan, 6.9℃; range: 4–11℃). On a 1.5 T MRI system, postmortem T1W-SE MRI of the brain was conducted in the 23 corpses prior to medico-legal autopsy. Next, T1 and T2 of the GM and WM at the level of the basal ganglia were determined in the same participants using inversion recovery and multiple SE sequences, respectively. The proton density (PD) was also calculated from the T1 and T2 images (in the same slice). T1W-SE image contrast between the GM and WM of all postmortem brains was inverted relative to the living brain. T1 (579 ms in GM and 307 ms in WM) and PD (64 in GM and 44 in WM) of the postmortem brain decreased compared with the living brain. While T1 of WM/GM remained below 1 even postmortem, the PD of WM/GM decreased. T2 (110 ms in GM and 98 ms in WM) of the postmortem brain did not differ from the living brain. The decrease in PD of WM/GM in the postmortem brain may be the major driver of contrast reversal between the GM and WM relative to the living brain. •WM/GM is preserved in postmortem brain T1W-SE images.•Postmortem brain T1 and PD are decreased.•Rates of postmortem water reduction differ between WM and GM.•Lower PD of postmortem brain WM drives contrast inversion between the GM and WM.